Parental Recognition of Bullying and Associated Factors Among Children After the Fukushima Nuclear Disaster: A 3-Year Follow-Up Study From the Fukushima Health Management Survey - Oe, Misari; Maeda, Masaharu; Ohira, Tetsuya; Itagaki, Shuntaro; Harigane, Mayumi; Suzuki, Yuriko; Yabe, Hirooki; Yasumura, Seiji; Kamiya, Kenji; Ohto, Hitoshi (Frontiers in Psychiatry, 2019)
This study examined parental recognition of bullying victimization and associated factors among evacuated children after the 2011 Fukushima Daiichi Nuclear Power Plant accident, using a 3-year follow-up data (wave 1: January 2012, wave 2: January 2013, wave 3: February 2014). The sample included the caregivers of 2616 children in the first–sixth grades of elementary school, who lived in one of the 13 municipalities that were the target areas of the Mental Health and Lifestyle Survey, conducted as part of the Fukushima Mental Health Management Survey. Across 3 years, around 80% of caregivers responded “not true,” 15% responded “somewhat true,” and 5% responded “certainly true” in response to a question about bullying victimization of their children. Being male was significantly associated with the parental recognition of bullying victimization at wave 1 and wave 3. At wave 1, experiencing the nuclear plant explosion was significantly associated with parental recognition of bullying victimization. Moreover, age at wave 3 was negatively associated with parental recognition of bullying victimization. Our findings will be helpful for establishing community- and school-based mental health care for children, parents, and teachers.